Finite Element Modelling Of The Wood Disintegration Using A Single-Pointed Cutting Tool - Kubík, Petr; Šebek, F (Morressier, 2017)
European wood industry is challenged by the demands on the increasing processing of hardwood due to the changes of species composition of the forests. The theory background of cutting force calculation during the hardwood disintegration is specific. Therefore, an advanced approach should be employed for the phenomena description. The experiments were carried out using a pendulum-based machine to approximately perform a linear cut on a European beech specimens. The cutting process was measured by a 3D force sensor and captured by a stereo vision with high-speed cameras. The numerical simulations were conducted accordingly using an explicit finite element method via the LS-DYNA software. The anisotropy was considered at every level u2013 within the elasticity, plasticity and failure. Moreover, the non-symmetric fracture behaviour was taken into account distinguishing between the different properties in tension and compression. The chip generation as well as force responses were compared. The fracture formation was reproduced quite accurately, yet the forces were not captured very well due to some oscillations, which are subject to the further studies.